2023
DOI: 10.3350/cmh.2022.0442
|View full text |Cite
|
Sign up to set email alerts
|

Nonalcoholic fatty liver disease and non-liver comorbidities

Abstract: Non-alcoholic fatty liver disease (NAFLD) is a chronic liver disease characterized by excess fat accumulation in the liver. It is closely associated with metabolic syndrome, and patients with NAFLD often have comorbidities such as obesity, type 2 diabetes mellitus, and dyslipidemia. In addition to liver-related complications, NAFLD has been associated with a range of non-liver comorbidities, including cardiovascular disease, chronic kidney disease, and sleep apnea. Cardiovascular disease is the most common cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 114 publications
(131 reference statements)
0
8
0
Order By: Relevance
“…MAFLD is also associated with congestive heart failure, which increases the risk of incident heart failure [ 109 ]. The presence of epicardial fat in MAFLD patients results in irregular energy metabolism in the left ventricle, which contributes to diastolic dysfunction [ 110 ].…”
Section: Liver–heart Axis In Mafldmentioning
confidence: 99%
See 1 more Smart Citation
“…MAFLD is also associated with congestive heart failure, which increases the risk of incident heart failure [ 109 ]. The presence of epicardial fat in MAFLD patients results in irregular energy metabolism in the left ventricle, which contributes to diastolic dysfunction [ 110 ].…”
Section: Liver–heart Axis In Mafldmentioning
confidence: 99%
“…Despite microbiota being a critical component involved in the pathophysiology of MAFLD, the most crucial factor determining the clinical outcome of MAFLD is cardiac manifestations, such as CVD. According to recent studies, MAFLD is an important risk factor for CVD, with a substantially increasing prevalence of CVD [ 25 , 109 ] ( Figure 3 ). Interestingly, dysregulation of the intestinal bacterial microbiota in patients with CVD and MAFLD could be a crucial contributing factor influencing the severity of metabolic dysfunction [ 124 ].…”
Section: Liver–heart Axis In Mafldmentioning
confidence: 99%
“…In summary, the excellent review by Manikat and Nguyen is a timely reminder of the strong association between NAFLD and various comorbidities. (32) While causality of the association remains a matter of debate, clinicians should be aware of the important comorbid conditions and arrange assessment and treatment as appropriate. Accordingly, the current Asia-Pacific guidelines recommend routine assessment for adiposity, blood pressure, glucose and lipids in patients with NAFLD.…”
Section: Management Implicationsmentioning
confidence: 99%
“…Obesity prevalence is estimated to be about 51% of NAFLD patients and about 82% of nonalcoholic steatohepatitis (NASH) patients, while the prevalence of diabetes, hypertension, and dyslipidemia are 22%, 40%, and 69% among NAFLD patients, with an even higher prevalence in NASH patients [ 1 ]. Other studies showed an increased risk of non-fatal cardiovascular events with an odds ratio of 2.52 in NAFLD patients compared to non-NAFLD patients, as well as an increased risk of congestive heart failure, atrial fibrillation, ischemic stroke, and chronic kidney disease [ 6 , 7 , 8 , 9 ]. However, there are only scant data published regarding the comparison of NAFLD patients and the general population.…”
Section: Introductionmentioning
confidence: 99%